2001
DOI: 10.1097/00006324-200105000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Smith-Kettlewell Institute (SKI) Longitudinal Study of Vision Function and Its Impact among the Elderly: an Overview

Abstract: We present an overview of a multifaceted longitudinal study of vision function and its interaction with daily activities, health, and well-being among 900 persons aged 58 to 102 years at the first visit. Standard vision measures as well as nonconventional tests designed to assess visual performance under the nonideal conditions encountered in everyday life were used. Here we summarize a few of the findings to date, with an emphasis on a direct comparison of declines in different aspects of vision function with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 15 publications
2
97
0
2
Order By: Relevance
“…A recent study by Aarts, Aries, Straathof and Van Hoof (2014) Visual problems differ among individuals and therefore demand specific lighting solutions to support individual nursing home residents in their daily activities. Selecting the appropriate environment and lighting conditions for all residents can be a complex task because of these individual differences (Brabyn, Schneck, & Haegerstrom-Portnoy, 2001). For example, bright light might be a problem for one resident, whereas another resident might require more light (Evans, Sawyerr, Jessa, Brodrick, & Slater, 2009;Jones & Van der Eerde, 2008;Brabyn, Schneck, & Haegerstrom-Portnoy, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Aarts, Aries, Straathof and Van Hoof (2014) Visual problems differ among individuals and therefore demand specific lighting solutions to support individual nursing home residents in their daily activities. Selecting the appropriate environment and lighting conditions for all residents can be a complex task because of these individual differences (Brabyn, Schneck, & Haegerstrom-Portnoy, 2001). For example, bright light might be a problem for one resident, whereas another resident might require more light (Evans, Sawyerr, Jessa, Brodrick, & Slater, 2009;Jones & Van der Eerde, 2008;Brabyn, Schneck, & Haegerstrom-Portnoy, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…82 There is considerable evidence that adults who are visually impaired have a poorer functional status in terms of ability to carry out both ADLs and IADLs than their fully sighted counterparts. 18,19,35,67,83,90,159 Lamoureux et al, for example, investigated the limitations in ADLs in 319 participants with a visual impairment with no visual rehabilitation history and found that reading, outdoor mobility, participation in leisure activities, and shopping were most limited. 90 Restricted mobility and orientation skills in individuals with visual impairment also make them more vulnerable to falls and associated complications such as hip fractures.…”
Section: A Consequences Of Visual Impairmentmentioning
confidence: 99%
“…Aging is associated with increasing prevalence of ocular diseases, and decline in different aspects of vision and vision-related functioning (Brabyn et al 2001). Despite these changes, the importance of vision to maintain postural control seems to increase with age (Woollacott 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among older adults the assessment of visual acuity alone may underestimate the degree of disability related to vision impairment because considerable changes may occur in visual functions other than acuity (Brabyn et al 2001). Many of these objectively measurable visual functions have found to associate with balance and mobility performance.…”
Section: Introductionmentioning
confidence: 99%